2011
DOI: 10.1371/journal.pone.0028964
|View full text |Cite
|
Sign up to set email alerts
|

The Predatory Ecology of Deinonychus and the Origin of Flapping in Birds

Abstract: Most non-avian theropod dinosaurs are characterized by fearsome serrated teeth and sharp recurved claws. Interpretation of theropod predatory ecology is typically based on functional morphological analysis of these and other physical features. The notorious hypertrophied ‘killing claw’ on pedal digit (D) II of the maniraptoran theropod Deinonychus (Paraves: Dromaeosauridae) is hypothesized to have been a predatory adaptation for slashing or climbing, leading to the suggestion that Deinonychus and other dromaeo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
156
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(171 citation statements)
references
References 68 publications
6
156
0
4
Order By: Relevance
“…Manning et al [32] concluded that “the feet and hands of dromaeosaurs functioned both for locomotion (walking, running, and climbing) and as prey capture/grappling devices”, though our data for digit III supports only a terrestrial interpretation. Deinonychus , however, does fall within the predatory category, suggesting that its foot may have been used in prey immobilisation behaviour analogous to modern Accipitridae [66], [69].…”
Section: Discussionmentioning
confidence: 99%
“…Manning et al [32] concluded that “the feet and hands of dromaeosaurs functioned both for locomotion (walking, running, and climbing) and as prey capture/grappling devices”, though our data for digit III supports only a terrestrial interpretation. Deinonychus , however, does fall within the predatory category, suggesting that its foot may have been used in prey immobilisation behaviour analogous to modern Accipitridae [66], [69].…”
Section: Discussionmentioning
confidence: 99%
“…With the specialization of the forelimbs for flight throughout the evolutionary history of birds, the capacity for manipulating objects progressively became relegated to the hindlimbs (Fig. Fowler et al (2011) hypothesized that selection for grasping prey, as evidenced by claw and foot morphology of deinonychosaurian ancestors of Aves, might have formed the basis for arboreal perching, and possibly even flapping flight. This formulates an intriguing departure, in that a few birds have achieved comparable levels of digital dexterity in the pes as other tetrapods have in the manus, and consequently most birds are restricted to the execution of a power grip.…”
Section: Grasping In Birdsmentioning
confidence: 99%
“…However, Iwaniuk & Whishaw (2000) suggested that prey-handling behaviour, even in basal amphibian lineages, might have been an important driving force for the evolution of manual grasping. Fowler et al, 2011) have been implicated in the evolution of pedal grasping across taxa. Gebo, 1985;Feduccia, 1999;Youlatos, 2008) and feeding (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Large comparative studies of mammals have used claws/unguals to determine locomotor, and in particular fossorial, adaptations (MacLeod & Rose, 1993). Modern claws are often correlated with those of nonavian dinosaurs to extrapolate paleo‐behavior (Burnham, Feduccia, Martin, & Falk, 2011; Fowler, Freedman, Scannella, & Kambic, 2011; Lautenschlager, 2014). These studies quantified claw morphology in several ways, including Euclidean distance measures, claw curvature based on triangles, outline‐based morphometrics, and digital modelling (respective examples in Ribas et al., 2004; Feduccia, 1993; MacLeod & Rose, 1993; Manning et al., 2009).…”
Section: Introductionmentioning
confidence: 99%